An Empirical analysis of use of TikTok by Management students in Pune city - Vhatkar, Mr. Abhijit Vhatkar; Mali, Dr. Nitin (The journal of contemporary issues in business and government, 2021)
Social Media use is continuously increasing. Various social media platforms such as Facebook, Instagram, YouTube etc. are dominating the market. New applications are also trying to move ahead in the competition. TikTok which is formally known as Music.ly has acquired user attention in last few years. TikTok is very famous among youngsters. It is used by students in large number. This research focus on use of TikTok by management students in Pune city.